JOGOS E BRINCADEIRAS INDÍGENAS NO ENSINO DA EDUCAÇÃO FÍSICA: desafios e perspectivas nos anos iniciais do ensino fundamental - Shreiber, Clodoaldo (2021)
In the face of the topic of education for ethnic-racial relations this dissertation presents the results of an action research developed at a 4th grade class from the early years of elementary education composed of 23 participants in which an intervention was performed, aiming mainly an analysis of the applicability of indigenous games and plays at Physical Education subject in the school context. Based on Barth’s (2000), Oliveira’s (2006), Luciano’s (2006) and Mota’s (1994; 2012) studies this paper approaches historical perspectives questioning the cultural boundaries caused by the colonization process that reflect on racist practices. The current research discusses the following inquiry: What is the applicability of indigenous games and plays at the implementation of Law 11.645/2008 to break racist perceptions, at Physical Education subject, in the school context of a 4th grade class from the early years of elementary education? It is addressed as a qualitative study, founded on the principles of educational ethnography. Accordingly to the theoretical-methodological instrumental for data analysis which, anchored in the assumptions of learningship constellations related to the Anthropology of Education, represent cognitive and emotional processes that lead thoughts and attitudes (DA SILVA, 2016; 2018). These experiences are lived within the community and are transmitted conscious or unconsciously as a type of learning in daily life (DA SILVA, 2016). The field notes along with the first sampling collected by the semi-structured instrument show stereotyped narratives built on references in which the participant’s learning relations stand. In the second sampling violence and racism recognition appear and both ethnicities emerge juxtaposed at a symmetrical level, undressing prejudice and revealing indigenous culture recognition along the history. Curriculum representativeness as a result of stigmatized groups effort is taken into consideration and understood as a great possible instrument to disarticulate oppressive cultural situations. Educational processes triggered during the research point to a way of possibilities and positive perspectives to notice and diminish racism. The indigenous games and plays learned while visiting Cacique Gregório Kaekchot Indigenous State School - EIEFEM (initials in Portuguese) at Terra Indígena Ivaí community indicated the applicability capable of providing new knowledge and experiences, creating changing possibilities at constellations, denaturalizing the violence and the historic denial suffered by indigenous. However, education for ethnic-racial relations needs to be more expansive, going 11 beyond school context and reaching other spaces and pedagogical environments that will interfere in learning relations with positive actions that may become a social practice.